Australian community pharmacists' perceptions of public health before the COVID-19 pandemic. (24th March 2021) - Hope, Denise L; Day, Georgie; Clements, Joshua; Hattingh, H Laetitia
Abstract: Background: Consensus is lacking regarding delivery of public health services in community pharmacy. Objective: The objective of this study was to explore pharmacists' perspectives on public health initiatives in community practice. Method: Australian community pharmacists were randomly sampled to participate in face-to-face, semi-structured interviews to explore public health definitions and perceptions. Key findings: Nine pharmacists participated early 2020, pre-COVID-19. Mean interview duration was 23 min. Results revealed little distinction between individual and public health services. Barriers to service provision were lack of time, remuneration, training, standards and privacy. Enablers opposed barriers, namely accessibility, improved funding, education, standardised services and consulting rooms. Conclusion: Improved clarity is required regarding the role that community pharmacists can assume in provision of public health.